2008
DOI: 10.1021/jp712039u
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Charge-Transfer-to-Solvent Dynamics of Iodide in Tetrahydrofuran. 2. Photoinduced Electron Transfer to Counterions in Solution

Abstract: Although they represent the simplest possible charge-transfer reactions, the charge-transfer-to-solvent (CTTS) dynamics of atomic anions exhibit considerable complexity. For example, the CTTS dynamics of iodide in water are very different from those of sodide (Na -) in tetrahydrofuran (THF), leading to the question of the relative importance of the solvent and solute electronic structures in controlling charge-transfer dynamics. In this work, we address this issue by investigating the CTTS spectroscopy and dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 72 publications
2
48
0
Order By: Relevance
“…As the CTTS state and the ground state of the solvated electron have a similar, s-like symmetry, each CTTS state likely evolves on a singlepotential energy surface all the way to the aqueous electron. This contrasts to the behaviour of, for example, Na À , whose CTTS state has a reversed, p-like symmetry such that a non-adiabatic transition is required to go from the reactant to the product state 13 . However, our findings show that the characteristic time scale of the dynamics (ultimately, the fluorescence lifetime) changes from excited ionic centre to the next because it strongly depends on the structure of the surrounding solvation cage at the time of photo-excitation.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…As the CTTS state and the ground state of the solvated electron have a similar, s-like symmetry, each CTTS state likely evolves on a singlepotential energy surface all the way to the aqueous electron. This contrasts to the behaviour of, for example, Na À , whose CTTS state has a reversed, p-like symmetry such that a non-adiabatic transition is required to go from the reactant to the product state 13 . However, our findings show that the characteristic time scale of the dynamics (ultimately, the fluorescence lifetime) changes from excited ionic centre to the next because it strongly depends on the structure of the surrounding solvation cage at the time of photo-excitation.…”
Section: Discussionmentioning
confidence: 84%
“…The valence electrons of ground-state anions are bound by the nucleus, but the excited states are bound by solvent polarization 1 . The CTTS states of halides rapidly decay by ejection of an electron, which is then stabilized by solvation, leaving a neutral halogen atom behind [2][3][4][5][6][7][8][9][10][11][12][13][14] . Atomic anions are ideal for studies of the electron-transfer dynamics to the solvent, because the solute lacks internal (nuclear) degrees of freedom, such that the process of CTTSmediated electron ejection is entirely governed by the structure and motions of the solvation shell.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary simulation studies of this system found that Na 0 clearly exists as a TCP in liquid THF, 18 in agreement with experimental interpretations. [1][2][3][4][13][14][15]19 In this work, we explore the molecular nature of the sodium TCP in significantly more detail. We find that the driving force for TCP formation lies in the creation of a tight solvation shell of ∼4 THF oxygens around the partially exposed Na + end of the TCP.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] For example, in the red-edge excitation of anions such as I − in THF, coupling of the local charge-transfer-to-solvent ͑CTTS͒ excited state to solvent-supported disjoint states with similar energies leads to photoejection of electrons to significant distances ͑ϳ6 nm͒ from the parent anion. 16 Another experimental signature of cavities is that the detached electrons produced after exciting nearly any anion in liquid THF-I − , 17 Na − , 14 K − , 18 or even the solvated electron itself 19 -appear after a ϳ0.5 ps time delay with their equilibrium spectrum. 20 This indicates that excited electrons relax directly into pre-existing solvent traps from the initially prepared solvent-supported excited state.…”
Section: Introductionmentioning
confidence: 99%